Applied aspects of the identity models application in the brand management system of domestic food industry enterprises - Holovan, Olha; Oliinyk, Oleksandr; Markova, Svitlana; Sukhareva, Kateryna (Management and Entrepreneurship: Trends of Development, 2024)
The relevance of the study is due to the fact that the food market in Ukraine is characterized by high competition both for sales markets and for limited resources due to significant dependence on market conditions. In the pre-war years, the coffee market, as a segment of the foodindustry of Ukraine, developed according to the global trend of production growth and a gradual increase in demand. One of the local coffee brands is the ISLA brand (Alta Plus LLC), which was developed in accordance with the taste preferences of Ukrainian consumers. Positioning the ISLA brand as a premium coffee for every day, the company targets consumers with an average and above - average income level, who appreciate the constant high quality of the drink.Creating a brand identity involves defining a unique set of its features. Brand identity helps establish a loyal relationship between the brand and the consumer by creating a value proposition that includes functional, emotional benefits, as well as a way of self-expression.During the conducted survey, it became clear that, according to the respondents, most of thefeatures that characterize the ISLA coffee brand as a personality according to J. Aaker's model ofbrand personality, refer to the characteristics of "Excitement" (energetic, modern, unique),"Sincerity" (friendly) and "Competence" (professional). Based on the results of the research, it has been proposed to put two archetypes as the basis of the ISLA brand : "Sage" and "Good guy", whichwill contribute to the unification of the target audience with the brand miss ion and help the company develop effective information appeals for target consumers.The ISLA brand identity should be formed on the basis of its presentation to consumers as areliable friend who tries to be always up-to-date, monitoring market trends, and energetic, charginghis environment with a positive charge.The study has found that the use of identity models in the brand management system of domestic food industry enterprises can be used to improve their marketing strategies in general and the formation of marketing communications.JEL класифікатор: А14, М31, М37, M39